[OP.1C.07] AORTIC PULSE WAVE VELOCITY PREDICTS SEVERE CARDIOVASCULAR EVENTS IN PATIENTS UNDERGOING CORONARY ANGIOGRAPHY. (September 2016) - Hametner, B.; Parragh, S.; Wassertheurer, S.; Weber, T.
Abstract : Objective: Pulse wave velocity (PWV) predicts cardiovascular events in different patient groups and in the general population. Its value in patients evaluated for suspected coronary artery disease (CAD) has never been clarified. In addition, the particular value of "true" aortic PWV (aoPWV) is unknown. Design and method: We prospectively measured aoPWV invasively during catheter pullback in patients undergoing diagnostic coronary angiography (aoPWVmeas), and we estimated aoPWV non-invasively from age, systolic blood pressure, and waveform characteristics, using the validated ARCSolver method (aoPWVestim). The extent of CAD was expressed by an angiographic score, comprising number of diseased vessels and stenosis grade. Primary endpoint was a combination of death, myocardial infarction, stroke, and unplanned coronary revascularization. Follow-up information was obtained from general practitioners, hospital records, and our national registry of death. Multivariable Cox models included age, gender, systolic and diastolic function, extent of CAD, mean or diastolic blood pressure, presence of diabetes, smoking, and creatinine. Results: We included 1095 patients (mean age 62.6 years, 34.7% women, 75.3% hypertensives, 20.4% diabetics, 16.4% smokers). 47.5% were diagnosed with CAD, mean angioscore was 2.2. 12.7% had impaired systolic function. During a mean follow-up duration of 4.7 years, 267 patients suffered from one of the components of the primary endpoint (134 deaths, 45 myocardial infarctions, 42 strokes, 108 revascularizations). In univariate analysis, an increase of 1 m/sec of aoPWV was associated with a 13% (aoPWVinv) and 16.7% (aoPWVestim) higher risk of the primary endpoint. In Cox proportional hazards models, invasively determined aoPWVmeas (p = 0.04) as well as non-invasively estimated aoPWVestim (p = 0.01) remained significantly associated with the primary endpoint. The other significant predictors were male gender, extent of CAD, diastolic function, diabetes and smoking, whereas mean or diastolic blood pressure showed an inverse relationship. Conclusions: Aortic stiffness, both measured invasively or estimated non-invasively, is an independent prognostic marker in patients with suspected CAD.